Design Features and Clinical Considerations of Orthopedic Knee Rehabilitation Exoskeletons: A Systematic Literature Review and Analysis - Wei, Zikun (My University, 2026)
As rehabilitation robotics expands from neurorehabilitation to orthopedics, the biomechanical suitability of existing devices remains unclear. This paper systematically reviews 57 wearable knee exoskeletons (2015–2025) to evaluate their clinical compatibility. It highlights the critical design divergence between the “repurposing strategy” of neuro-derived systems and the “specialized design philosophy” of orthopedic-specific solutions. Using a novel five-dimensional evaluation framework, this study reveals a significant design "mismatch." While systems relying on a generalist, neuro-adapted approach offer advanced control, their architectures often lack the kinematic compatibility and structural support required for vulnerable orthopedic joints. In contrast, "specialized" designs have seen explosive growth, prioritizing unilateral modularity and anatomical protection. However, a "valley of death" persists in translational research: over 60% of orthopedic-specific devices remain at Technology Readiness Level (TRL) 4, failing to reach clinical patient trials. The study concluded that most current cases of transplanting neurological rehabilitation equipment for orthopedic use cannot address the specific needs and limitations of orthopedics. Future development should adopt an "orthopedic-first" philosophy— prioritizing multi-DOF stability, modular adaptability, and pain-aware control. These shifts are imperative to reduce adverse events and optimize treatment outcomes in orthopedic rehabilitation. In addition, another systematic review should be conducted on mature and cuttingedge neurosurgical exoskeletons that do not claim to include orthopedic rehabilitation functions to analyze their potential to meet orthopedic rehabilitation needs.
Keywords: Orthopedic Rehabilitation; Knee Exoskeleton; Systematic Review; Mechanical Design; Clinical Compatibility